2016
DOI: 10.3109/10641955.2015.1116553
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study of the hemodynamic behavior of ophthalmic arteries in postpartum preeclamptic women: A doppler evaluation

Abstract: The aim of this study was to evaluate the hemodynamic behavior of the ophthalmic artery by means of the Doppler ultrasound, in postpartum preeclamptic women. It was an observational prospective study with 44 postpartum preeclamptic women (group 1) and 49 postpartum normal women with normal blood pressure and with no previous illnesses known (group 2). All the pregnant women had a Doppler ultrasound exam of the ophthalmic artery in the immediate puerperium, that is, 10 days for the delivery (time 1). Group 1 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 33 publications
2
6
0
1
Order By: Relevance
“…The only changes of significance were a reduction in the end diastolic ophthalmic artery velocity, and consequently a reduced TAMaxV and increased PI and RI. This is a novel finding, as although other authors have compared postnatal ophthalmic artery Doppler variables in a cohort of previously preeclamptic women with normotensive controls, this is the first study to observe the impact of delivery within the same cohort. The apparent increase in vascular resistance may reflect a healthy cerebrovascular response to the normal changes in cardiac output after delivery, as homeostasis is reestablished through a rise in systemic vascular resistance to prepregnancy levels.…”
Section: Discussionmentioning
confidence: 70%
“…The only changes of significance were a reduction in the end diastolic ophthalmic artery velocity, and consequently a reduced TAMaxV and increased PI and RI. This is a novel finding, as although other authors have compared postnatal ophthalmic artery Doppler variables in a cohort of previously preeclamptic women with normotensive controls, this is the first study to observe the impact of delivery within the same cohort. The apparent increase in vascular resistance may reflect a healthy cerebrovascular response to the normal changes in cardiac output after delivery, as homeostasis is reestablished through a rise in systemic vascular resistance to prepregnancy levels.…”
Section: Discussionmentioning
confidence: 70%
“…Our findings are consistent with the observation of reduced vascular resistance in transcranial Doppler studies of the cerebral arteries of women with PE reported by Riskin‐Mashiah et al 18 and in the ophthalmic artery by Hata et al 19 , 20 and Diniz et al 21 Sato et al 22 reported declining vascular resistance and an inverse correlation with MAP in the retinal vessels in late pregnancy in normal subjects using laser Doppler flowmetry. Alves Borges et al 23 reported reduced resistance in the ophthalmic artery in post-partum PE versus control subjects. Belfort et al, 24 however, reported that whereas resistance was negatively correlated with MAP in normal pregnancies, it was positively correlated with MAP in the CRA and ophthalmic artery in PE.…”
Section: Discussionmentioning
confidence: 98%
“…After delivery, the changes in the ophthalmic artery Doppler parameters of pre‐eclamptic women may take time to resolve, with a recent study demonstrating persistent differences up to 3 months postpartum in comparison with women with normotensive pregnancy. This serves to reinforce our evolving understanding that many features of pre‐eclampsia may take much longer than the conventional 6 weeks to resolve.…”
Section: Introductionmentioning
confidence: 91%